Effect of treatment and aging on mechanical properties of date palm fiber-filled nitrile rubber composites - Noor S. Alghamdi; Othman Y. Alothman; Mohammad Jawaid; Ubair Abdus Samad; Ramzi Khiari; Maher M. Alrashed (Journal of Engineered Fibers and Fabrics)
The aim is to investigate the effect of chemical treatment and aging on the mechanical and thermal properties of nitrile butadiene rubber (NBR) composites reinforced with date palm fiber (DPF). The fibers were treated with 5 wt% NaOH and silane (Si69) to improve fiber-matrix adhesion. Treated composites showed a 25% increase in tensile strength (from 8.5 to 10.6 MPa at 40 wt.% DPF) and enhanced thermal stability, with decomposition onset shifting from ~200°C to 220°C. Dynamic mechanical analysis (DMA) showed increased storage modulus and damping performance, with treated composites displaying a higher tan δ at ~1% strain. Aging tests revealed superior resistance to hot air and ozone exposure, with tensile strength retention above 90%, whereas oil aging led to a mechanical reduction due to fiber swelling. Fourier Transform Infrared Spectroscopy (FTIR) confirmed improved fiber-matrix bonding, while scanning electron microscopy (SEM) showed reduced fiber pull-out in treated samples. Glass transition temperature ( T g ) remained stable, ranging from −12.8°C to −9.6°C for different fiber loadings. The thermal study demonstrated that fibers do not hinder the rubber chin movement, and thermal treatment improves the fibers’ thermal stability.